Charcot Arthropathy of the Shoulder Associated with Syringomyelia: A Report of 2 Cases - Rodrigues, Mateus de Sousa; Coelho, Camila Maciel Martins; Pereira, Alexsandro da Silva; Neto, Fernanda Tavares; Silva, Wanderson Ricardo Serapião da; Neto, Heverty Rocha Alves; Maciel, Cícero do Juazeiro Job; Lima, Cícero Santos de; Feitosa, Randson Ranilson Modesto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2024)
Charcot arthropathy of the shoulder caused by syringomyelia is a unusual degenerative disorder, frequently misdiagnosed and with few cases described in the literature. The diagnosis is made by clinical evaluation and radiological examinations with radiography and magnetic resonance imaging. However, the correct diagnosis and treatment is possible by carefully medical evaluation and can improve patient symptoms. Therefore, this study aimed to report two cases of Charcot arthropathy caused by syringomyelia. After achieving correct neurosurgical evaluation and magnetic resonance imaging, the diagnosis was made. The first case is a 53-year-old man with a click on his right shoulder for at least 12 months, associated with local edema, pain and limitation of joint range of motion. The second is a 45-year-old man with pain in the right upper limb and difficulty moving the joint for at least 24 months, associated with progressive worsening of the collection and edema in the ipsilateral upper limb. Posterior fossa decompression was performed, with symptoms relief after surgery. Posterior fossa decompression is a treatment that seems to be effective in reducing symptoms, especially when the diagnosis is early. However, this type of treatment still remains controversial, requiring further studies.
Keywords: charcot arthropathy; neurogenic arthropathy; syringomyelia; shoulder